Моделі та інструментальні засоби для створення піксельних картин - Мідіна, С. С. (ХНУРЕ, 2024)
The work examines graphic editors for creating pixel paintings, and also considers ways to create pixel paintings both with the help of graphic editors and with the help of artificial intelligence and converting photos into pixel style. A microcontroller-based pixel picture model using a mobile application was developed and investigated. Methods of connecting a mobile device to a microcontroller are considered.
Keywords: створення піксельних картин; pixel paintings